Pengaruh Eco-label dan Environmental Awareness terhadap Keputusan Pembelian Produk Air Minum dalam Kemasan (AMDK) pada Konsumen di Kabupaten Pati - M. Zainal Mustofa Riski; Nani Nuraeni (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the influence of eco-labels and environmental awareness on purchasing decisions of bottled drinking water (AMDK) among consumers in Pati Regency. The study employed a quantitative approach with an explanatory research design. The population consisted of bottled drinking water consumers in Pati Regency, and a sample of 100 respondents was determined using the Lemeshow formula and a purposive sampling technique. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression with IBM SPSS Statistics. The results showed that eco-labels had a positive and significant effect on purchasing decisions, with a t-value of 7.931 and a significance value of 0.000. Furthermore, environmental awareness also had a positive and significant effect on purchasing decisions, with a t-value of 5.699 and a significance value of 0.000. Simultaneously, eco-labels and environmental awareness significantly influenced purchasing decisions, as indicated by an F-value of 64.403 and a significance value of 0.000. The Adjusted R Square value of 0.562 indicates that both variables explain 56.2% of the variation in purchasing decisions, while the remaining proportion is influenced by other factors outside the research model. These findings indicate that the presence of eco-labels and higher consumer environmental awareness can increase purchasing decisions for bottled drinking water products; therefore, companies should strengthen green marketing strategies and environmental education for consumers.